2008
DOI: 10.1051/0004-6361:200809724
|View full text |Cite
|
Sign up to set email alerts
|

A grid of MARCS model atmospheres for late-type stars

Abstract: Context. In analyses of stellar spectra and colours, and for the analysis of integrated light from galaxies, a homogeneous grid of model atmospheres of late-type stars and corresponding flux spectra is needed. Aims. We construct an extensive grid of spherically-symmetric models (supplemented with plane-parallel ones for the highest surface gravities), built on up-to-date atomic and molecular data, and make it available for public use. This includes "CN-cycled" models with C/N = 4.07 (solar), 1.5 and 0.5, C/O r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
2,791
0
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,608 publications
(2,826 citation statements)
references
References 89 publications
23
2,791
0
12
Order By: Relevance
“…We found that, in the range of D4000 n relevant for our analysis, while the absolute values of D4000 n are different, the slopes are not strongly dependent on the α-enhancement, with a percentage difference between 2% and 8% 6 . This results is confirmed also studying single stellar population models based on MARCS theoretical libraries [99], using solar metallicity and [α/F e] = 0, 0.4 (Claudia Maraston, private communication); in this case the difference in D4000 n is extremely small, on average only ∼ 0.5%, with a percentage variation in the slope of ∼ 8%. As a final remark, it has to be considered also that since in our analysis we consider the most massive ETGs, these galaxies will have quite similar enhancements, so that considering this effect will not introduce an additional systematic error, but just a shift in the slope.…”
Section: A3 the α−Enhancementsupporting
confidence: 71%
“…We found that, in the range of D4000 n relevant for our analysis, while the absolute values of D4000 n are different, the slopes are not strongly dependent on the α-enhancement, with a percentage difference between 2% and 8% 6 . This results is confirmed also studying single stellar population models based on MARCS theoretical libraries [99], using solar metallicity and [α/F e] = 0, 0.4 (Claudia Maraston, private communication); in this case the difference in D4000 n is extremely small, on average only ∼ 0.5%, with a percentage variation in the slope of ∼ 8%. As a final remark, it has to be considered also that since in our analysis we consider the most massive ETGs, these galaxies will have quite similar enhancements, so that considering this effect will not introduce an additional systematic error, but just a shift in the slope.…”
Section: A3 the α−Enhancementsupporting
confidence: 71%
“…The atmospheric models were obtained by interpolation in the grid of MARCS LTE models (Gustafsson et al 2008). The spectrum synthesis code used is described in Barbuy et al (2003) and Coelho et al (2005).…”
Section: Calculations Of C N and O Abundancesmentioning
confidence: 99%
“…We used a grid of OSMARCS atmosphere models in spherical symmetry (Gustafsson et al, 2008) Spite (1967) and continuously improved since then. Abundances were first computed for each individual line and the uncertainties on the EW measurements given by DAOSPEC are propagated into uncertainties on individual abundances.…”
Section: Determination Of Stellar Parameters and Abundancesmentioning
confidence: 99%